1985
DOI: 10.1128/jb.162.1.98-101.1985
|View full text |Cite
|
Sign up to set email alerts
|

In vivo synthesis of histidine by a cloned histidine ammonia-lyase in Escherichia coli

Abstract: Histidine ammonia.lyase catalyzes the first step in histidine catabolism, the deamination of histidine to urocanate and ammonia. In vitro experiments have shown that histidine ammonia-lyase also can catalyze the reverse (amination) reaction, histidine synthesis, relatively efficiently under extreme reaction conditions (4 M NH4OH, pH 10). An Escherichia coli hisB deletion strain was transformed with a pBR322 derivative plasmid (pCB101) containing the entire KkbsieUa aerogenes histidine utilization (hut) operon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…We usually cultured the cells for 4-8 h to avoid the tracers added to the medium being metabolized and incorporated into thiamin biosynthesized in the cells. However, it has been reported that urocanic acid is transported only slowly in Salmonella tyhpimurium and Klebsiella aerogenes ( 17 ). Therefore we also incubated the cells for 20 h (data not shown), under the same conditions as used by Zeidler; we obtained the same results as after (Fig.…”
Section: Incorporation Of [ 13 C]formate Into the Pyrimidine Moiety Isupporting
confidence: 55%
See 1 more Smart Citation
“…We usually cultured the cells for 4-8 h to avoid the tracers added to the medium being metabolized and incorporated into thiamin biosynthesized in the cells. However, it has been reported that urocanic acid is transported only slowly in Salmonella tyhpimurium and Klebsiella aerogenes ( 17 ). Therefore we also incubated the cells for 20 h (data not shown), under the same conditions as used by Zeidler; we obtained the same results as after (Fig.…”
Section: Incorporation Of [ 13 C]formate Into the Pyrimidine Moiety Isupporting
confidence: 55%
“…Alternatively, if the permeability of the cell membrane to formamide was inhibited in the presence of urocanic acid, the incorporation of 13 C-formamide would be decreased and it would seem as if incorporation of the label into the pyrimidine moiety were inhibited by urocanic acid. Further, it has been reported that histidine is synthesized from urocanic acid in an Escherichia coli mutant (17). There is a possibility that some of the urocanic acid was converted to histidine, which inhibited the incorporation of [ 13 C]formamide into the pyrimidine moiety in Zeidler's study (14).…”
Section: Incorporation Of L -[ 13 C]histidine Into the Pyrimidine Moimentioning
confidence: 97%
“…The hutH gene, encoding the cytosolic enzyme HAL, is considered an ancient and basal gene, participating in a core metabolism for the degradation pathway of l -histidine. It distributes broadly in bacteria and promotes them to utilize histidine as carbon and nitrogen sources ( Fuchs and Kane, 1985 ). The loss of the HUT pathway in bacteria only leads to their lack of sufficient capacity for the utilization of histidine, but this is not lethal.…”
Section: Discussionmentioning
confidence: 99%
“…Media and cultural conditions. Exponential cultures were routinely grown (9) in Luria broth (LB) medium (17), with tetracycline (12.5 p.g/ml) or kanamycin (50 p.g/ml) added for plasmid-containing strains. Cell extracts were prepared as described previously (9) in 50 mM potassium phosphate buffer, pH 6.3 (buffer A), and were used as a source of chitinase.…”
Section: Methodsmentioning
confidence: 99%